The Influence of Growth Mindset, Product Innovation, and Social Media Utilization on Business Development with Social Support as a Mediating Variable in MSMEs in Lalabata Village, Soppeng Regency - Mustari, Mustari; Rijal, Syamsu; Amri, A. Dhiya Iradah; Ahmad, Muhammad Ihsan Said; Arisah, Nur (International Journal of Business, Law, and Education, 2024)
This study examines the impact of growth mindset, product innovation, and social media utilization on business development and the role of social support as a mediating variable in MSMEs in Lalabata District, Soppeng Regency. This study used a quantitative approach with purposive sampling technique and involved 100 respondents. The data analysis technique applied was Partial Least-Square Structural Equation Modeling (PLS-SEM). The results showed that growth mindset, product innovation, and social media utilization all have a positive influence on business development. Social support also has a positive impact on business development. In addition, social support mediates the relationship between growth mindset, product innovation, and social media utilization with business development in MSMEs in Lalabata District, Soppeng Regency